The adoption of green energy technologies: The role of policies in an international comparison - Spyridon Arvanitis; Michael Peneder; Christian Rammer; Tobias Stucki; Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2016)
We contribute to the existing research about policy-induced technology adoption in several ways. First, we suggest a new survey design to measure the energy-related policy environment. Second, we simultaneously estimate the policy effects for the adoption propensity and the adoption intensity simultaneously and, third, we conduct an international comparison of the policy effects. Based on a representative sample of firms for Austria, Germany, and Switzerland we find that policies in all three countries essentially promote the adoption of technologies and they are practically ineffective for the intensity, which poses a great challenge to future policy designs. Voluntary agreements or demand related factors are among the most important drivers for the adoption propensity of green energy technologies. Given the current institutional framework in the surveyed countries, subsidies are more effective in Austria, taxes are more effective in Germany, and demand related factors are relatively more effective in Switzerland.
Keywords: 330